1996
DOI: 10.1007/bf00146331
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chromospheric features to UV irradiance variability from spatially-resolved Ca II K spectroheliograms

Abstract: We have digitized the Ca II K spectroheliograms, observed at the National Solar Observatory at Sacramento Peak, for the period 1980 (maximum of solar cycle 21), 1985 (minimum of solar cycle 21), 1987 (beginning of the ascending phase of solar cycle 22), 1988 and 1989 (ascending phase and maximum of solar cycle 22), and 1992 (declining phase of solar cycle 22). A new method for analyzing the K spectroheliograms has been developed and applied to the K images for the time interval of 1992. Using histograms of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Fredga 1971; Kariyappa & Sivaraman 1994;Kariyappa & Pap 1996;Worden et al 1998a;Giorgi et al 2005;Ermolli et al 2009a). However, in most cases acquisition of these exposures started many years after the start of solar observations.…”
Section: Introductionmentioning
confidence: 99%
“…Fredga 1971; Kariyappa & Sivaraman 1994;Kariyappa & Pap 1996;Worden et al 1998a;Giorgi et al 2005;Ermolli et al 2009a). However, in most cases acquisition of these exposures started many years after the start of solar observations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the solar energy flux changes over a solar cycle. It has been shown that the long-term irradiance variations are attributable to the changing emission of bright magnetic elements (Foukal & Lean 1988;Kariyappa & Pap 1996;Worden et al 1998;Kariyappa 2000Kariyappa , 2008Veselovsky et al 2001;Kumara et al 2012), whereas the short-term irradiance variations are directly associated with active regions as they evolve and move across the solar disk (Lean 1987). To understand and clarify the difference between the observed and modelled irradiance variability, to know the underlying physical mechanisms of solar irradiance variability, and to estimate the contribution of various coronal features to EUV and UV irradiance, a detailed and accurate image analysis of spatially resolved observations from space is required.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Arcetri, Kodaikanal, and Mt Wilson Ca ii K historic observations have recently been digitized (Ulrich et al 2004;Makarov et al 2004;Marchei et al 2006), and other similar series are now being processed as well. Some Ca ii K series already underwent digitization and analysis in the 1990s, when selected (regularly spaced) spectroheliograms or almost entire series were converted at 2 pixel −1 (e.g., Ribes & Mein 1985 (p. 282); Kariyappa & Pap 1996;Caccin et al 1998;Worden et al 1998) or 5 pixel −1 (Foukal 1996) resolution, respectively. Defects in and decay of spectroheliogram photographic plates, missing photographic calibration, and undocumented changes of the instrumentation lead to various artifacts in and problems with the historic data (Zharkova et al 2003;Fuller et al 2005;, which are avoided in the full-disk images taken by the most recent synoptic observing programs.…”
Section: Introductionmentioning
confidence: 99%